Pemanfaatan Panas Buang Industri Untuk Membangkitkan Otec (Ocean Thermal Energi Conversion) - Andi Hendrawan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
Industrial waste heat is waste heat that is used to cool production machinery. This waste heat will be discharged into the environment with a relatively warm temperature which is above 30o C. Cilacap as an industrial city certainly has become one of the problems that must be solved. Because if not properly managed, it will damage the marine ecosystem. Utilization of industrial exhaust heat is very important, one of which is to be used to generate OTEC. You do this by transferring industrial exhaust heat to the OTEC system, which is to the evaporator that is used to evaporate the ammonia sample flow.